Intelligent Leadership
XIII, 212 p.
Keywords: Effective educational leadership, while highly contextualized, is more and more recognized as a crucial input and process variable that determines to a very large extent the outcomes for educational organizations. This book pulls together the thinking of 16 educators with diverse backgrounds and experiences, all of whom hold keen interests in harnessing the forces that can improve educational opportunity for students. Becoming an effective education leader requires more than a passing knowledge of leadership theory; it also requires knowledge of what works in education and an on-going commitment to thinking about how leadership dynamics and pedagogical theory intersect within contextual realities. Intelligent Leadership: Constructs for Thinking Education Leaders is intended to stimulate the thinking of every educator who aspires to influence decision-making and to provide direction to their school, district or institution.